High-pressure processing treatment of beef burgers: Effect on Escherichia coli O157 inactivation evaluated by plate count and PMA-qPCR - Rey, Maria De Los Angeles (2022)
Este trabajo fue apoyado por el Ministerio de Ciencia y Tecnología, Agencia Nacional de Promoción de la Investigación, desarrollo tecnológico y la innovación (MINCYT PICT-2015-0291).